EFFECTIVENESS OF WASTE MANAGEMENT IN THE SERVICE ENVIRONMENT OF MAKASSAR CITY - Mutaharah, Shofyah; Akib, Haedar; Halim, Didin; Johansyah, Oky Nur Pratiwi (Universitas Negeri Makassar, 2025)
This study aims to determine the Effectiveness of Waste Management at the Makassar City Regional Environmental Office. This type of research is qualitative descriptive. Data collection was carried out by means of observation, interviews, and documentation. Data analysis uses interactive model analysis, namely data condensation, data presentation, and conclusion drawn. The results of the study show that the Effectiveness of Waste Management at the Makassar City Regional Environment Agency has not been effective. Judging from the dimensions of goal achievement, integration, adaptation and can be seen from the aspects of planning, organizing, implementing, and supervision, namely 1) The achievement of goals in the aspect of supervision has not been effective because the waste transportation system still faces significant challenges, such as the facilities and infrastructure currently available are still inadequate, such as garbage trucks that already have a schedule but often there are delays in transporting waste that resulting in the pile of garbage tending to increase. 2) Integration in the planning aspect where the community has not or still lacks awareness in carrying out environmental cleanliness even though socialization or directions have been held. 3) Adaptation to the planning aspect where some people have not received the education provided immediately only requires habits in the community and the existing budget is still not able to meet the needs in one time procurement of waste management.